Evaluating the Effectiveness of an English Tutorial Program for Non-English Majors - Zharif, Yusuf Hafizh; Adityarini, Hepy (JELITA, 2025)
This study aims to evaluate the effectiveness of the English Tutorial Program (ETP) organized by Lembaga Bahasa dan Ilmu Pengetahuan Umum (LBIPU), starting from the challenges faced by ETP tutors in teaching speaking and students' perceptions of the effectiveness of ETP in improving their speaking skills. This mixed-methods study employed a sequential exploratory design and used interviews and questionnaires to collect data. The study involved 33 interview participants, including tutors and students, while questionnaires were distributed to 82 non-English students at Universitas Muhammadiyah Surakarta. The data were analyzed qualitatively using the coding method and quantitatively with descriptive statistics. The findings showed that challenges such as scheduling conflicts and students' varying levels of understanding were identified. Most students reported that ETP improved their speaking ability, increased their confidence, and provided useful feedback from the tutors. It is concluded that ETP is effective in supporting English competency among non-English-speaking students, although improvements are needed in the coordination and dissemination of the program.